INTERTEXTUALITY IN THE DEATH OF A PILOT: THE KUBERNETES ARISTOS IN LUCIAN’S VERAE HISTORIAE. - Nicholas D. Newman (Journal of Ancient History and Archaeology, 2015)
In Lucian’s Verae Historiae, Lucian ensures the success of his voyage by providing the very best supplies and equipment for his men. As part of his preparation he hires on the best pilot that money could buy, this pilot is only heard from at one other point in the narrative, at his death in the belly of the sea monster. This paper examines the intertextual context of the pilot’s death and how Lucian uses it to further the juxtaposition of himself with that greatest of liars, Odysseus.